2022
DOI: 10.3389/fpsyg.2022.933432
|View full text |Cite
|
Sign up to set email alerts
|

Innovation capabilities and human development competitiveness in education sector: Evidence from UAE

Abstract: Innovation capabilities and human development in education sector is one of the key focused areas in United Nations Sustainable Development Goals. The current research is novel to integrate and address such constructs in single theoretical framework. Grounded in Human Capital Theory, this study aims to investigate the role of innovation capabilities in human development competitiveness in the education sector of UAE. Based on the qualitative research approach, data were collected through interviews with 70 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…The United Arab Emirates (UAE) government has invested heavily in becoming a global HE hub, attracting foreign students through international branch campuses and programs (Karabchuk et al, 2021). The COVID-19 pandemic impacted HE in the UAE as institutions adapted to online learning (Mukasa et al, 2021), compelling HE institutions in the UAE to switch to online learning to protect students' safety while continuing the broader transition to entirely online learning (Al Dulaimi et al, 2022). This impacted the academic experience of learners and teachers and the provision of educational continuity and quality (Omar et al, 2021).…”
Section: Higher Education In the United Arab Emiratesmentioning
confidence: 99%
“…The United Arab Emirates (UAE) government has invested heavily in becoming a global HE hub, attracting foreign students through international branch campuses and programs (Karabchuk et al, 2021). The COVID-19 pandemic impacted HE in the UAE as institutions adapted to online learning (Mukasa et al, 2021), compelling HE institutions in the UAE to switch to online learning to protect students' safety while continuing the broader transition to entirely online learning (Al Dulaimi et al, 2022). This impacted the academic experience of learners and teachers and the provision of educational continuity and quality (Omar et al, 2021).…”
Section: Higher Education In the United Arab Emiratesmentioning
confidence: 99%
“…The results obtained through the case study demonstrated favorable outcomes, including the creation of new knowledge, the sharing of information among colleagues, the development of inventive solutions, and the utilization of technological assets. Lastly, Al Dulaimi et al (2022) reviewed innovation capabilities and human development competitiveness in education in the context of the United Arab Emirates, focusing on human capital theory as the basis for investigation for deriving the key variables through a qualitative survey.…”
Section: Background Of the Studymentioning
confidence: 99%